PERANCANGAN PROTOTYPE APLIKASI MOBILE FRIZFOO MENGGUNAKAN METODE USER CENTERED DESIGN - limputra, Juan kristo; Sudirman; Thayf, Mohammad Sofyan S (KHARISMA Tech, 2024)
This research involves the design of a mobile application prototype called Frizfoo using the User-Centered Design (UCD) approach to ensure the alignment between design and user needs. Primary data was obtained through interviews and observations of five Frizfoo users, using the "magic number five" approach to identify usability issues. The analysis results showed significant problems with some tasks. Furthermore, the research measured the time required to complete tasks (Time on Task) and the error rate (Errors) made by users. It was found that one user experienced delays in completing some tasks, attributed to factors such as age and lower technological skills. However, these delays were still within acceptable limits. The average error rate for all tasks was approximately 5.30%. The testing results indicated that the designed interface of the mobile application had low error rates, efficient task completion times, and a high level of user satisfaction. Adjustments and design improvements made based on the testing results had a significant positive impact on the performance and responsiveness of the mobile application prototype. This research provides a clearer insight into the quality of the Frizfoo application prototype design and serves as a foundation for further development that better aligns with user needs.